Quantification of trace 227Ac and other radionuclidic impurities in mass-separated 225Ac samples produced at CERN-MEDICIS - Jake D. Johnson; Cyril Bernerd; Frank Bruchertseifer; Thomas E. Cocolios; Marie Deseyn; Charlotte Duchemin; Michael Heines; Max Keppens; Laura Lambert; Nathan Meurrens; Ralf E. Rossel; Thierry Stora; et al. (Scientific Reports)
Abstract 225Ac is a promising candidate medical radionuclide for targeted alpha therapy of advanced stage cancers. One of the main production pathways is the high-energy proton spallation of thorium-based targets, that requires an efficient, nuclide-selective separation method to recover 225Ac from hundreds of co-produced spallation and fission products. The main radioactive contaminant of concern is 227Ac (T1/2 = 21.8 years), that could preclude extensive medical use if not significantly suppressed. In this work, 225Ac samples were produced by mass separation of radioactive ion beams extracted from proton-irradiated thorium-based targets. The activity of 225Ac and other possible contaminants of the samples were measured using complementary gamma- and alpha-decay spectrometry methods, while 227Ac activity was calculated by performing alpha-decay spectrometry of recoiled progeny from the sample. Using this novel method, accurate measurement of trace 227Ac activity in 225Ac samples was performed much faster than with conventional spectrometry techniques, thanks to its 10,000-fold increase in relative sensitivity. The end of collection activity ratio of 227Ac to 225Ac in two samples from irradiated targets were determined to be $$2.00(10) × 10^{-6}$$ and $$2.7(4) × 10^{-6}$$ respectively, three orders of magnitude below the 227Ac activity in 225Ac products obtained through radiochemical separation. The high separation factor of 225Ac over 227Ac suggests the suitability of mass-separated accelerator-based 225Ac for medical use.